Explain using words how you know a fraction is equivalent to another fraction

Answers

Answer 1
Answer: Two fractions are equivalent if

(a) Both the numerator (top) and denominator (bottom) of each fraction are the same. For example, two-fifths (2/5) of one thing is equivalent to two-fifths (2/5) of another thing.

(b) The numerator and denominator of one fraction can both be multiplied by the same number to equal the numerator and denominator of the other fraction. An example of this would be two-thirds (2/3) and six-ninths (6/9). Both two and three can be multiplied by three (3) to equal the numbers in their respective spots in the fraction six-ninths (6/9). (Two multiplied by three is six, three multiplied by three is nine.)

OR

(c) The numerator and denominator of one fraction can be divided by the same number to equal the numerator and denominator of the other fraction, like with six-tenths (6/10) and three-fifths (3/5). Both six and ten, when divided by two, are equal to three and five, respectively.

Answer 2
Answer: If you multiply the top and the bottom by the same number

Related Questions

a dvd box set includes 3 thriller movies and 2 comedies. use t to represent the cost of each thriller and c to representv the cost of each comedy. write and simplify an expression that represents the total cost of 6 box sets.
What time is 46 minutes before 2:10 pm
How to solve 6w 30; 5, 6, 7
PLEASE HELP SOLVE! PICTURE ABOVE​
1. Find x, the missingside length in the righttriangle.3677

What is the additive inverse of the polynomial? -7y^2+x^2y-3xy-7x^2

Answers

Answer:

Additive inverse is  (7y² - x²y + 3xy + 7x²).

Step-by-step explanation:

Let the additive inverse of the given polynomial be Y.

Therefore as per definition of additive inverse of any polynomial the addition of a polynomial and additive inverse of any polynomial is always zero.

So Polynomial + additive inverse polynomial = 0

(-7y² + x²y - 3xy - 7x²) + Y = 0

Y = -(-7y² + x²y - 3xy - 7x²) = (7y² - x²y + 3xy + 7x²)

So the additive inverse of the polynomial will be (7y² - x²y + 3xy + 7x²).

Answer:

The answer is A

Step-by-step explanation:

The additive inverse is basically the opposite symbol for the numbers.

So, therefore:

What is the additive inverse of the polynomial?

-7y^2 + x^2y - 3xy - 7x^2

The answer to this would be

7y^2 - x^2y + 3xy + 7x^2

2 friends want to equally share 4/3 feet of rope.What length of rope should ea friend get?

Answers

Each friend should get 2/3 feet of rope because 4/3 is the same thing as 1 1/3 so 4/3 / 2 = 2/3 or 1 1/3 / 2 = 2/3. Hope that helps!
Each friend would get 2/3 feet of rope

Of the students in Rosales dance class 29 out of 58 have participated in dance class before. about how many of her students have participated in dance class before?A.0
B.1/2
C.1
D.2

Answers

Answer:

0.5 or 1/2

Step-by-step explanation:

The answer is 0.5 or one half, because you are trying to figure out the amount of other students who have participated. So we know that 29 out of 58 participated, so you just do 29/58 and you get 1/2.

Hope this helps, have a good day. c;

Hat is the solution to the equation 3/3(4c + 16)=2c+9 ?

c =

Answers

if it is (3)/(3(4c+16))=2c+9, go to AAAAAA
if it is ((3)/(3))(4c+16)=2c+9, go to BBBBB

AAAAAAAAA
(3)/(3(4c+16))=2c+9
(1)/(4c+16)=2c+9
times 4c+16 to both sides
1=(2c+9)(4c+16)
distribute
1=8c^2+68c+144
minus 1 both sides
0=8c^2+68c+143
use quadratic formula
c=(-17- √(3) )/(4) or (-17+ √(3) )/(4)




BBBBBBBBBBBB
(3/3)(4c+16)=2c+9
1(4c+16)=2c+9
4c+16=2c+9
minus 2c both sides
2c+16=9
minus 16 both sides
2c=-7
divide both sides by 2
c=-7/2
c=-3.5





if it is (3)/(3(4c+16))=2c+9,
c=(-17- √(3) )/(4) or (-17+ √(3) )/(4)


if it is ((3)/(3))(4c+16)=2c+9, c=-3.5



Acutly its really simple Let's solve your equation step-by-step.3/3(4c+16)=2c+9Step 1: Simplify both sides of the equation.3/3(4c+16)=2c+9Simplify: ((3/3)(4c)+(3/3)(16)=2c+9(Distribute)4c+16=2c+9Step 2: Subtract 2c from both sides.4c+162c=2c+92c2c+16=9Step 3: Subtract 16 from both sides.2c+16−16=9−162c=−7Step 4: Divide both sides by 2.2c/2=−7/2c=−7/2Answer:c=−7/2

What is the formula of volume ofba rhombic prism

Answers

Volume=the\ base\ area\ multiplied\ by\ the\ height\n\nif\ the\ base\ is\ a\ rhombus,\ \ then\ the\ base\ area= (1)/(2)\cdot e\cdot f \ \ \n\nand\ \ \ e,f\rightarrow\ the\ length\ of\ the diagonals\ of\ a\ rhombus\n\nV=(1)/(2)\cdot e\cdot f \cdot h\n\nand\ \ h\rightarrow\ the\ height\ of\ prism

Answer:

Hight times base equals area

Step-by-step explanation:

What's the sum of 74 836 and 2 67

Answers

If those are decimals the answer is 77. 506.
74,836 + 267 is 75,203

Hope this helps!